Socialization of the Use of Mobile-Based Online Public Complaints System in Kebun Kelapa Village - Ramadhan, Zuhri; Iskandar, Iskandar; Kurniawan, Heri (International Conference on Sciences Development and Technology, 2023)
This service aims to provide socialization and training on the use of a mobile-based online public complaint system in Kebun Kelapa Village. This training is carried out using practical and participatory methods, allowing participants to learn and implement the use of Android / mobile in the online complaint process. It is hoped that in the future the results of this service will make it easier for the community to provide suggestions, input and criticism regarding the performance of village officials both in Kebun Kelapa Village and Langkat District Office. By implementing this mobile-based online method, it will be easier for the community to convey their aspirations to village officials without having to come to the village office. The positive impact of this training can be observed from the increase in people who are able to use online applications via their respective mobile phones. . Apart from that, this training also opens up new opportunities for village communities to utilize the potential of village communities with existing technological developments and effectively support sustainable village economic development.